2022
DOI: 10.1093/g3journal/jkac100
|View full text |Cite
|
Sign up to set email alerts
|

The Nab2 RNA-binding protein patterns dendritic and axonal projections through a planar cell polarity-sensitive mechanism

Abstract: RNA binding proteins support neurodevelopment by modulating numerous steps in post-transcriptional regulation, including splicing, export, translation, and turnover of mRNAs that can traffic into axons and dendrites. One such RBP is ZC3H14, which is lost in an inherited intellectual disability. The Drosophila melanogaster ZC3H14 ortholog, Nab2, localizes to neuronal nuclei and cytoplasmic ribonucleoprotein granules, and is required for olfactory memory and proper axon projection into brain mushroom bodies. Nab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 84 publications
5
13
0
Order By: Relevance
“…The ZC3H14 protein is evolutionarily conserved among eukaryotes and has been studied in Mus musculus ( Zc3h14 ) (Guthrie et al ., 2011; Pak et al ., 2011; Soucek et al ., 2016), Caenorhabditis elegans ( sut-2 ) (Guthrie et al ., 2009), Sacchromyces cerevisiae (Nab2) (Anderson et al ., 1993; Green et al ., 2002; Hector et al ., 2002; Marfatia et al ., 2003; Kelly et al ., 2007; Kelly et al ., 2010; Schmid et al ., 2015; Soucek et al ., 2016), Sacchromyces pombe (Nab2) (Grenier St-Sauveur et al ., 2013), and Drosophila melanogaster (Nab2) (Pak et al ., 2011; Kelly et al ., 2016; Fasken et al ., 2019; Lee et al ., 2020; Corgiat et al ., 2021; Corgiat et al ., 2022; Rounds et al ., 2022; Jalloh and Lancaster et al ., 2023). These studies have collectively uncovered molecular and neuronal functions for this conserved ZnF Pab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ZC3H14 protein is evolutionarily conserved among eukaryotes and has been studied in Mus musculus ( Zc3h14 ) (Guthrie et al ., 2011; Pak et al ., 2011; Soucek et al ., 2016), Caenorhabditis elegans ( sut-2 ) (Guthrie et al ., 2009), Sacchromyces cerevisiae (Nab2) (Anderson et al ., 1993; Green et al ., 2002; Hector et al ., 2002; Marfatia et al ., 2003; Kelly et al ., 2007; Kelly et al ., 2010; Schmid et al ., 2015; Soucek et al ., 2016), Sacchromyces pombe (Nab2) (Grenier St-Sauveur et al ., 2013), and Drosophila melanogaster (Nab2) (Pak et al ., 2011; Kelly et al ., 2016; Fasken et al ., 2019; Lee et al ., 2020; Corgiat et al ., 2021; Corgiat et al ., 2022; Rounds et al ., 2022; Jalloh and Lancaster et al ., 2023). These studies have collectively uncovered molecular and neuronal functions for this conserved ZnF Pab.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies show that Nab2 interacts with Fmr1, the fly homolog of Fragile X Syndrome RBP, FMRP (Wan et al ., 2000), and that these two RBPs co-regulate mushroom body morphology and olfactory memory through a mechanism likely to involve translational repression of shared Nab2-Fmr1 target RNAs (Bienkowski et al ., 2017). Beyond the brain, Nab2 limits dendritic branching of class IV dorsal dendritic arborization (ddaC) sensory neurons through a mechanism involving the planar cell polarity (PCP) pathway (Corgiat et al ., 2022), suggesting that Nab2 controls RNA targets encoding regulators of the actin cytoskeleton. Our recent work studying the effect of Nab2 loss on the brain transcriptome revealed that Nab2 is required for proper splicing of ~150 mRNAs (Jalloh and Lancaster et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Nab2 is expressed in adult and pupal KCs (no data is available for Frontiers in Physiology frontiersin.org larval KCs). The MBs in Nab2 −/− flies display high penetrance of α lobe-missing and β lobe overextension phenotypes that can be rescued by specific expression of wild-type Nab2 in the KCs (Kelly et al, 2016;Corgiat et al, 2022). Removing one copy of Vang, Appl, or dsh significantly rescues the Nab2 homozygous mutant MB phenotypes, supporting that Nab2 regulates KC axonal development by tuning down PCP signaling (Corgiat et al, 2022).…”
Section: Wnt-pcp Pathwaymentioning
confidence: 98%
“…RNA-binding protein Nab2 has been found to regulate the levels of PCP components. Comparing the proteomes of wild-type and Nab2 homozygous mutant flies revealed that PCP pathway proteins, including Vang, APPL, and several putative PCP effectors, are differentially expressed in Nab2 mutant flies (Corgiat et al, 2022). Nab2 is expressed in adult and pupal KCs (no data is available for Frontiers in Physiology frontiersin.org larval KCs).…”
Section: Wnt-pcp Pathwaymentioning
confidence: 99%
See 1 more Smart Citation